Peran Pengawasan terhadap Pengelolaan Keuangan di Dinas Sosial Transmigrasi dan Tenaga Kerja Kabupaten Mamasa - Bachtiar Bachtiar (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2021)
This paper aims to find out how the development of the government apparatus is directed at creating a more efficient, effective, clean and authoritative apparatus and is able to carry out all general government and development tasks as well as possible based on the spirit and attitude of service to the community, nation and state. In this connection, the ability of government officials to plan, implement, supervise, and control development needs to be improved. The supervisory function in financial management is an important part of financial management itself, in order to ensure the suitability and accuracy of budget expenditures. Therefore, the function of internal control in the context of financial management in Indonesia, included as a function of controlling the use and receipt of finance. This study aims to determine the procedures for implementing supervision in the management of regional finances at the Transmigration Social Service and the Mamasa Regency workforce. And the extent of the role of supervision on the effectiveness of regional financial management at the Social Transmigration and Manpower Office of Mamasa Regency. The results of the study indicate that the role of supervision for the effectiveness of the financial management of the Transmigration Social Service and manpower can be said to be very instrumental because through this internal control all budget items which include routine expenditures and development expenditures can be in accordance with the Order of Spending Money by the treasurer, so that the function of supervision This has been placed as a means for the proper use of the issued budget funds.